Recent Progress on Two-Dimensional Nanoflake Ensembles for Energy Storage Applications - Xia, Huicong; Xu, Qun; Zhang, Jianan (Nano-Micro Letters, 2018)
The rational design and synthesis of two-dimensional (2D) nanoflake ensemble-based materials have garnered great attention owing to the properties of the components of these materials, such as high mechanical flexibility, high specific surface area, numerous active sites, chemical stability, and superior electrical and thermal conductivity. These properties render the 2D ensembles great choices as alternative electrode materials for electrochemical energy storage systems. More recently, recognition of the numerous advantages of these 2D ensemble structures has led to the realization that the performance of certain devices could be significantly enhanced by utilizing three-dimensional (3D) architectures that can furnish an increased number of active sites. The present review summarizes the recent progress in 2D ensemble-based materials for energy storage applications, including supercapacitors, lithium-ion batteries, and sodium-ion batteries. Further, perspectives relating to the challenges and opportunities in this promising research area are discussed. Highlights: 1 In this review, we emphasize the recent developments on two-dimensional nanoflake ensembles and their applications for enhanced electrochemical performance in supercapacitors, lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, and zinc-ion batteries. 2 An overview of recent advances in three-dimensional hierarchical structures from two-dimensional nanoflake ensembles with controllable shape and compositions is provided. 3 Enhanced electrochemical energy storage performance based on assemblies of these two-dimensional nanoflake ensembles is discussed in detail.